2018
DOI: 10.1038/s41467-018-04472-6
|View full text |Cite
|
Sign up to set email alerts
|

Activity of acetyltransferase toxins involved in Salmonella persister formation during macrophage infection

Abstract: Non-typhoidal Salmonella strains are responsible for invasive infections associated with high mortality and recurrence in sub-Saharan Africa, and there is strong evidence for clonal relapse following antibiotic treatment. Persisters are non-growing bacteria that are thought to be responsible for the recalcitrance of many infections to antibiotics. Toxin–antitoxin systems are stress-responsive elements that are important for Salmonella persister formation, specifically during infection. Here, we report the anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
111
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(116 citation statements)
references
References 34 publications
3
111
2
Order By: Relevance
“…In turn, the secreted KRS could promote the production of pro-inflammatory cytokines in THP-1 cells, such as IL-8, IL-1β, and TNF-α. Differing from Shiga toxins, the acetyltransferase toxins produced by Salmonella Enteritidis and Typhimurium inhibited translation in macrophages by acetylation of aminoacyl-tRNAs, thereby inducing Salmonella persister formation during infection 107 . In conclusion, host ARSs not only participate in the HIV assembly, but also protect against bacterial and viral infections by modulating the immune responses, indicating that ARSs play an important role in infectious diseases.…”
Section: Arss In Bacterial Infectionmentioning
confidence: 99%
“…In turn, the secreted KRS could promote the production of pro-inflammatory cytokines in THP-1 cells, such as IL-8, IL-1β, and TNF-α. Differing from Shiga toxins, the acetyltransferase toxins produced by Salmonella Enteritidis and Typhimurium inhibited translation in macrophages by acetylation of aminoacyl-tRNAs, thereby inducing Salmonella persister formation during infection 107 . In conclusion, host ARSs not only participate in the HIV assembly, but also protect against bacterial and viral infections by modulating the immune responses, indicating that ARSs play an important role in infectious diseases.…”
Section: Arss In Bacterial Infectionmentioning
confidence: 99%
“…Next, we investigated Salmonella cells during macrophage infection. The fate of Salmonella after entering macrophages is known to be heterogeneous: some cells survive and proliferate, whereas others lyse in the harsh intracellular environment [3032]. Previous studies have suggested that variations in Salmonella cell wall structure may play an important role in heterogeneous infection outcomes [33], but it has been challenging to measure such phenotypic variations in situ .…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that more than 100 autoimmune or chronic inflammatory human diseases affect 5%-10% of the population worldwide. 8 Moreover, defects in the enzymes that catalysed tRNA modification and aminoacylation contributed to the abnormalities in the immune system. 2,3 Transfer RNAs (tRNAs), traditionally considered as adaptor molecules, can translate messenger RNAs (mRNAs) into proteins by delivering various amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…7 Acetyltransferase toxins secreted by Salmonella suppressed protein translation by acetylation of aminoacyl-tRNAs and thus induced the persister state in human macrophages. 8 Moreover, defects in the enzymes that catalysed tRNA modification and aminoacylation contributed to the abnormalities in the immune system. 9,10 Therefore, the study of tRNAs in the setting of immunity has proven particularly meaningful.…”
Section: Introductionmentioning
confidence: 99%